Intelligent Cyber-Physical System for Shaping the Needs of the Internet of Things - V. M. Trembach; A. A. Mikryukov; I. S. Vachmanov; T. G. Trembach (Открытое образование (Москва))
The purpose of the study. The article discusses the research and further development of modern cyber-physical systems of the Internet of Things (CPS IoT). Researchers in the field of psychology, logic, lin- guistics, philosophy, for the study of artificial intelligence, used many different models of this phenomenon of “man”. Currently, the search for new approaches continues. One of the interesting approaches lies in the development of the application of cognitive mechanisms that a person uses in solving everyday tasks. The application of methods of gestalt processing of states of the CPS IoT worldview is considered to solve an ever-expanding range of tasks. Hybrid or, as they are also called, combined models can be used for gestalt processing to solve various tasks of cyber-physical systems of the Internet of Things related to forecasting indexes of the functioning of socio-economic systems. To do this, you can use a long-known approach to hybrid- ization, the essence of which is to split the entire set of initial data into subsets of initial data. The main stages of gestalt processing and one of the initial stages – the formation of a need are shown. The significant moments of the organization of interaction of CPS IoT modules with the environment are presented. In the demo example, the CPS IoT of the estate museum is considered. The main elements of the formation of the need for CPS IoT in organizing and conducting excursions are described.Materials and methods of research. To solve problems within the framework of gestalt processing of CPS IoT, new methods and developments of specialists in the field of intelligent systems are re- quired. Hybrid, combined models can be used for gestalt processing for various tasks of cyber-physical systems of the Internet of Things related to forecasting indexes of the functioning of socio-economic systems. You can use a long-known approach to hybridization, the essence of which is to split the entire set of initial data into subsets of initial data. It is possible to use gestalt processing within the framework of a holistic approach when splitting into subsets of the initial data - clusters. The cognitive approach uses sensory images, concept-representations, concept-scenarios and gestalts. The CPS IoT gestalt can be considered as one of the approaches to solving modern problems within the framework of Industry 4.0 technology. The article describes intelligent cyber-physical systems using methods of gestalt processing of their states - a picture of the world. Approaches to the use of needs and one of the many approaches to the formation of the needs of cyber-physical systems of the Internet of Things are considered.Results. Within the framework of the cognitive approach, con- cepts-representations of CPS IoT for arising (emerging) needs and their fixation are proposed. After fixing the need, as the main stages of its formation, the following are highlighted: concretization of the event, collection of relevant initial data for the need; formation (folding of perceived information) of the gestalt: checking the state of the necessary elements, searching for resources in the environment; organization of contact with the environment. These stages of the formation of the need relate to CPS IoT of any nature and are fo- cused on any tasks of the Internet of Things. It is advisable to save scenarios for the formation of needs for possible reuse in the future. The demo example shows an example of the formation of a need for CPS IoT during an excursion.Conclusion. The article considers a cognitive approach related to the use and development of intelligent cyber-physical systems for the Internet of Things and the Internet of everything. The main stages of the formation of the need for CPS IoT are considered. The implementation of the proposed approach, the development and use of gestalt concepts will allow reflecting CPS IoT with new emergent properties.